Generation of High‐Titer Defective HSV‐1 Vectors. Issue 1 (1st January 2013) - Neve, Rachael L.; Lim, Filip
Abstract: Basic Protocol 1 describes the generation of helper virus stocks. Preparation of recombinant amplicon vector particles by transfection of amplicon and superinfection of helper virus into cells, and harvesting of packaged particles, is delineated in Basic Protocol 3. Thorough characterization of each amplicon viral vector stock involves measuring (1) the helper virus plaque‐forming units per ml (pfu/ml) on 2‐2 cells and (2) the amplicon stock infectious units per ml (iu/ml) on PC12 cells. The Support Protocols detail methods for determining titers of helper virus by plaque assay, and of amplicon stocks by vector assay. Curr. Protoc. Neurosci . 62:4.13.1‐4.13.15. © 2013 by John Wiley & Sons, Inc.